Functional properties of rice flour and its effect on conformational changes in the structure of wheat dough and bread - Shevchenko, Anastasiia; Litvynchuk (Vorontsova), Svitlana (My University, 2022)
Situation in food industry in Ukraine and in the world has undergone significant changes during the last decade, especially the last year, which was caused by the military aggression of the russian federation. Diseases, particularly of the gastrointestinal tract, such as inflammatory bowel disease, have developed rapidly. In this regard, it is worth looking for approaches to diet therapy, which involves reducing dietary fiber in the diet. A promising raw material for inclusion in the rec-ipe of bakery products is rice flour. The water absorbing capacity of rice flour was 60% hig her compared to wheat flour. The study of the water holding capacity indicator showed the redistribution in the interaction of flours with water. For rice flour, this indicator increased by 27% compared to wheat flour. Fat absorbing capacity is higher for wheat flour than for rice flour by 7%, the increase in the ability to hold fat was by 35% for rice flour. The advantages of wheat flour over rice flour in terms of the ability to form constant emulsions were shown: the emulsifying ability index of wheat flour was higher by 80% than of rice flour, emulsifying stability — by 210%. The analysis of the spectra of the control sample of dough and the dough samples with 10% and 20% replacement of wheat flour with rice flour showed that the control sample of the dough and sample with 10% and 20% rice flour after kneading have practically the same spectra. The spectra of the dough control sample after 3.5 hours of fermentation and sample with 10% and 20% replacement have lover value of the relative reflection coefficient. But dependence that spectra of control samples are lover persists. Spectra of bread samples regardless of the presence of rice flour overlap but aspire to the spectrum of control sample of the dough after 3.5 hours of fermentation.
Keywords: bread; rice flour; inflammatory bowel diseases; infrared spectroscopy; functional properties; кафедра технології хлібопекарських і кондитерських виробів; кафедра фізики та професійної безпеки